General Genetics - Cienfuegos Rivas, Eugenia Guadalupe (Libros UAT, 2018)
Genetics is the science that studies the laws of inheritance and variation in plants and animals. The publication of the articles by Gregor Mendel in 1866 is one of the most important events in the history of genetics; however, these documents were ignored until 1900 when they were found and published by three biologists (Hugo de Vries in Holland, Carl Correns in Germany and Erick Von Tschermack in Austria) who gave credit to Gregor Mendel, who was named The Father of Genetics. . These facts and those that preceded it set the tone for the science of Biology to have great advances in the area of ??Genetics. From 1900, the discovery of the structure of DNA and the new technologies of multiplication of genetic material, marked a new era where biotechnological tools play a very important role. Currently biotechnology has advanced considerably, the basic knowledge of the laws of inheritance and variation are fundamental to understand the mechanisms of transmission of genes and their manipulation. They are the tools that every student in the agricultural area must know to understand the biology of protein synthesis and its role in the productive behavior of plants and animals. This book is the result of a compilation of basic educational material whose main foundation is to teach the undergraduate student the physical and chemical basis of the inheritance. For reading this book requires that the reader has the basic knowledge about biology and chemistry that allows the teaching-learning process of the topics contained in the work.